Optimiere Deine Meeting-Produktivität (Assemble You, 2022)
Welcome to our Assemble You Learning Podcast While teamwork and collaboration are essential aspects of business and professional development, surveys have found that meetings can be the biggest waste of time at work. We'll look at how you can reduce the number of meetings you have and how you can design meetings so they deliver actionable results. You will also learn how to better manage the preparation and follow-up of meetings. Learning Outcomes Learn how to lead a productive meeting Learn what to do outside of the actual meeting to get the most value from the time invested.